2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27839
|View full text |Cite
|
Sign up to set email alerts
|

Board # 36 : Engineering Faculty Perspectives on Student Mathematical Maturity

Abstract: He also has a courtesy appointment as a research assistant professor with the Department of Curriculum & Instruction. He earned his Ph.D. in Electrical and Computer Engineering from the University of Illinois at Urbana-Champaign as a Mavis Future Faculty Fellow and conducted postdoctoral research with Ruth Streveler in the School of Engineering Education at Purdue University. His research interests include creating systems for sustainable improvement in engineering education, conceptual change and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…This result corroborated evidence with interviews with engineering faculty, who stated that only a small fraction of the rules learned in calculus are used regularly in engineering (Faulkner, et al 2017;Ferguson, 2012;Ganter & Barker, 2004;Varsavsky, 1995;Yeatts & Hundhausen, 1992). Only the simplest rules of calculus are applied in circuits and statics.…”
Section: Complexity Of Functionssupporting
confidence: 66%
See 3 more Smart Citations
“…This result corroborated evidence with interviews with engineering faculty, who stated that only a small fraction of the rules learned in calculus are used regularly in engineering (Faulkner, et al 2017;Ferguson, 2012;Ganter & Barker, 2004;Varsavsky, 1995;Yeatts & Hundhausen, 1992). Only the simplest rules of calculus are applied in circuits and statics.…”
Section: Complexity Of Functionssupporting
confidence: 66%
“…Mathematics faculty are aware that engineers are dissatisfied with calculus outcomes and want to change to please these client disciplines, but are themselves not well-versed enough in the applications of calculus to do so alone (Cui, 2006;Yeatts & Hundhausen, 1992). Previous studies have found that both mathematics and engineering faculty are unaware of what goes on in the others' classrooms (Faulkner et al, 2017;Varsavsky, 1995;Willcox & Bounova, 2004;Yeatts & Hundhausen, 1992). Future studies could repeat this analysis for more courses such as introductory physics, chemistry, dynamics, and thermodynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematics faculty are aware that engineers are dissatisfied with calculus outcomes and want to change to please these client disciplines, but are themselves not well-versed enough in the applications of calculus to do so alone [77,91]. Previous studies have found that both mathematics and engineering faculty are ignorant of what goes on in the others' classrooms [61,60,91,114]. Future studies could repeat this analysis for more courses such as introductory physics, chemistry, dynamics, and thermodynamics.…”
Section: Discussionmentioning
confidence: 95%